Utilization of Used Cooking Oil into Aromatherapy Candles: Implementation of Circular Economy as a Business Idea among University Students - Anang Setiawan; Fadil Muhammad; Nurul Chalisa Majiding; Tenri Sayu Puspitaningsih Dipoatmodjo; Rahmat Burhamzah; Josafat Gracia Ginting; Khusnul Patima; Ahmad Rais (PT. Global Research Collaboration, 2025)
The management of used cooking oil remains a serious environmental issue, as it is classified as hazardous waste that can contaminate soil and water if disposed of improperly. On the other hand, used cooking oil holds high economic potential and can be utilized through the circular economy concept to create value-added products. This community service program aimed to enhance the awareness and skills of students from the Faculty of Economics and Business, Universitas Negeri Makassar, in processing used cooking oil into aromatherapy candles as a form of green entrepreneurship. The training was conducted through socialization, education, demonstration, and hands-on practice using purified used cooking oil mixed with stearic acid and essential oils. Evaluation results showed that 85% of participants improved their understanding of waste management and candle-making techniques, while 72% expressed interest in developing this product as a sustainable business idea supported by digital marketing. This activity successfully integrated environmental education, entrepreneurial innovation, and student empowerment through the application of circular economy principles. Therefore, the program not only provided a solution to the waste oil problem but also fostered sustainable and socially responsible entrepreneurial mindsets among students.